2016
DOI: 10.1016/j.aap.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Review of safety and mobility issues among older pedestrians

Abstract: a b s t r a c tAlthough old people make up an extremely vulnerable road-user group, older pedestrians' difficulties have been studied less extensively than those of older drivers, and more knowledge of this issue is still required. The present paper reviews current knowledge of older-adult problems with the main components of pedestrian activity, i.e., walking and obstacle negotiation, wayfinding, and road crossing. Compared to younger ones, old pedestrians exhibit declining walking skills, with a walking spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 196 publications
3
49
0
Order By: Relevance
“…However, walking and cycling are not always easy activities for older people to undertake. Very little research has been carried out on walking and cycling in later life from the transportation point of view, especially in terms of barriers affecting the use of these two modes, since researchers have focused mainly on safety of older drivers [76]. Nonetheless, three main issues can be identified: health, safety and the built environment.…”
Section: Walking and Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, walking and cycling are not always easy activities for older people to undertake. Very little research has been carried out on walking and cycling in later life from the transportation point of view, especially in terms of barriers affecting the use of these two modes, since researchers have focused mainly on safety of older drivers [76]. Nonetheless, three main issues can be identified: health, safety and the built environment.…”
Section: Walking and Cyclingmentioning
confidence: 99%
“…Unlike other transport modes (e.g., car) that can compensate for health impairments [20], walking and cycling can be more directly affected by health problems. In their review, Tournier, Dommes and Cavallo [76] identified health barriers affecting older pedestrians according to sensory, cognitive and physical impairments. Sensory impairments are associated with the risk of falling, reduced perception of fixed and moving objects, problems in detecting approaching vehicles and difficulties in distinguishing vehicles from other aspects of the road environment.…”
Section: Walking and Cyclingmentioning
confidence: 99%
“…5 While walking is the most common physical activity of older people it exposes the walker to increased risk of accident and falling. 6 Reaction time decreases with age, and hence elderly people are less able to recover their balance in sufficient time after an accidental foot misplacement. Hospitalisation data from Australia (Figure 1) shows the elderly (465 years) are much more frequently injured due to a fall then younger people.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to their younger counterparts, old pedestrians exhibit declining walking skills, with a walking speed decrease, less stable balance, less efficient wayfinding strategies, and a greater number of unsafe road crossing behaviours. These difficulties are linked to age-related changes in sensorial, cognitive, physical, and self-perception abilities [6].…”
Section: Introductionmentioning
confidence: 99%